19. CHARACTERISTICS OF TONGUE IN PATIENTS WITH KNEE PAIN DUE TO KNEE OSTEOARTHRITIS (Vietnam Journal of Community Medicine, 2024)
Objectives: Survey of the characteristics of tongue in patients with knee pain due to knee osteoarthritis.Subject and methods: The cross-sectional study was conducted on 391 patients with knee pain due to knee osteoarthritis. Tongue images were taken on these patients, then analyzed by automatic tongue diagnosis system ZMT-1A at the office of Department of Basic Traditional Medicine, Faculty of Traditional Medicine, University of Medicine and Pharmacy at Ho Chi Minh City.Results: The main characteristics of tongue-body color are a dark-purple tongue (58.3%) and, a thin tongue (50.6%). In terms of coating tongue, little/no coating accounted for 74.2%, white coating 31.5%, and wet coating accounted for 47.6%. The difference of tongue-body shape and tongue with blood stasis between pain levels (VAS) are statistically significant (p
Keywords: Tongue diagnosis, knee osteoarthritis